EVALUATION OF MEDICATION COMPLIANCE IN PATIENTS WITH CONGESTIVE HEART FAILURE IN YEMEN - MOHAMMED AL-ZAAZAAI, AL-ZAAZAAI ET AL ALI AHMED; AL-AMRANI, MANSOUR A.; ALAKHALI, KHALED M.; ALJABER, NOURADDEN (International Journal of Pharmacy and Pharmaceutical Sciences, 2019)
Objective: Non-compliance with heart failure medication is related to the highest mortality, morbidity, and health-care costs. The objective of this study was to evaluate medication compliance with patients with congestive heart failure. Methods:Inpatients of the cardiac care unit and medical ward of Republican Hospital, German Hospital, Revolutionary Hospital, and Chinese–Yemeni Friendship Hospital were recruited for this study. The study was conducted on patients that were diagnosed as having congestive heart failure and were receiving treatment. Questionnaires were distributed and personal interviews to evaluate the patients’ compliance was conducted to determine the reasons for their non-compliance in taking drugs. Results: Of 86 patients, 44% (n = 38) reported compliance and 56% (n = 48) reported non-compliance. The distribution of the patients in terms of sex was as follows: among men, 41% (n = 24) were compliant and 59% (n = 35) were non-compliant; among women, 52% (n = 14) were compliant and 48% (n = 13) were non-compliant. In addition, smoking status was too significantly linked with non-compliance (P = 0.001). Furthermore, the status of chewing of khat tree leaves was also significantly associated with non-compliance (P = 0.007). Conclusion: This study indicates that the reasons for non-compliance with medications among patients can be attributed to lack of education, chewing of khat tree leaves, lack of health insurance, and cigarette smoking. Therefore, healthcare professionals should create strategies to address these reasons in order to increase medication compliance with patients in heart failure.